2007
DOI: 10.1108/00070700710732547
|View full text |Cite
|
Sign up to set email alerts
|

The diet of prisoners in England

Abstract: Purpose -The purpose of this research is to establish whether the meals provided by the prison service enable prisoners to follow government guidelines on nutrition and healthy eating, and the extent to which they do so. Design/methodology/approach -A total of eight prisons, four male (category A, B and C), two female and two young offenders' institutes were randomly identified and visited. Data collection involved taking three days of cyclical menus, the institution's recipes and methods and standard or avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…In contrast, whole grains were not provided in accordance with MyPlate guidelines, nor were fruits, vegetables, and dairy products, a finding also reported by Collins and Thompson (2012) for prisons in South Carolina. Inadequate provisions of fruits and vegetables also have been documented in studies of menus used in correctional facilities in the United Kingdom and Australia (Edwards et al, 2007;Williams et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, whole grains were not provided in accordance with MyPlate guidelines, nor were fruits, vegetables, and dairy products, a finding also reported by Collins and Thompson (2012) for prisons in South Carolina. Inadequate provisions of fruits and vegetables also have been documented in studies of menus used in correctional facilities in the United Kingdom and Australia (Edwards et al, 2007;Williams et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, existing literature about prison food and nutrition offers guidance on how to comply with nutritional standards, legal requirements, and budgetary and security issues (e.g. Brisman, 2008; Cray, 2001; Edwards, Hartwell, Reeve, & Schafheitle, 2007; Foster, 2006; Herbert, Plugge, Foster, & Doll, 2012; Stein, 2000; Tammam, Gillam, Gesch, & Stein, 2012; Wakeen, 2008), and describes interventions to improve prisoner diets and help inmates lose weight (Eves & Gesch, 2003; Khavjou et al, 2007; Nikolas, 2000; Robinson, Haupt-Hoffman, Stewart, Schneider, Hamm, & Garrison, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…This study fills gaps in the literature by presenting perspectives of two groups who discussed the practical issues of quality of food and physical activity. Other studies to date capture the perspective of either the prison administrators or prisoners (Edwards et al, 2007; Herbert et al, 2012; Smith, 2002; Vanhouche, 2015), but not older prisoners. By highlighting the voices of the participants on this topic, we underline the challenges and provide recommendations to address the noted problems.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of meals provided to prisoners in England revealed that prisoners have access to a nutritionally balanced diet, but they lack understanding of what comprises a healthy diet (Edwards, Hartwell, Reeve, & Schafheitle, 2007). Other studies investigating prison food services discussed problems with limited budgets and special dietary requirements (Collins & Thompson, 2012; Elger, 2016; Foster, 2006).…”
Section: Introductionmentioning
confidence: 99%